2016
DOI: 10.1371/journal.pone.0168355
|View full text |Cite
|
Sign up to set email alerts
|

Activated p53 with Histone Deacetylase Inhibitor Enhances L-Fucose-Mediated Drug Delivery through Induction of Fucosyltransferase 8 Expression in Hepatocellular Carcinoma Cells

Abstract: BackgroundThe prognosis of advanced hepatocellular carcinoma (HCC) is dismal, underscoring the need for novel effective treatments. The α1,6-fucosyltransferase (fucosyltransferase 8, FUT8) has been reported to accelerate malignant potential in HCC. Our study aimed to investigate the regulation of FUT8 expression by p53 and develop a novel therapeutic strategy for targeting HCC cells using L-fucose-mediated drug delivery.MethodsBinding sites for p53 were searched for within the FUT8 promoter region. FUT8 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In the 2 remaining cohorts, including GSE39084 and GSE35896, FUT8 mRNA seemed to be consistently highly expressed in p53 wild-type tumors compared to those with mutant p53, although it did not reach statistical significance probably due to the relatively small sample size in those cohorts. Those findings might seem consistent with our hypothesis that FUT8 expression can be regulated by p53, as the recent report has demonstrated that FUT8 is a direct transcriptional target of wild-type p53 [ 14 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the 2 remaining cohorts, including GSE39084 and GSE35896, FUT8 mRNA seemed to be consistently highly expressed in p53 wild-type tumors compared to those with mutant p53, although it did not reach statistical significance probably due to the relatively small sample size in those cohorts. Those findings might seem consistent with our hypothesis that FUT8 expression can be regulated by p53, as the recent report has demonstrated that FUT8 is a direct transcriptional target of wild-type p53 [ 14 ].…”
Section: Resultssupporting
confidence: 93%
“…This suggests that alterations of p53 can cause dysregulation of FUT8 mRNA levels possibly through transcriptional mechanism. As the FUT8 promotor region is likely to carry the responsive element of wild-type p53 [ 14 ], loss of wild-type p53 function due to TP53 mutations might be responsible for the altered FUT8 mRNA expression. However, this finding was not confirmed in FUT8 protein levels, in which no association was found between FUT8 expression and abnormal p53 expression by IHC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the silencing of FUT8 in CAFs and the upregulation of It was showed by the GSEA that the low expression of FUT8/CF led to inhibition of both extrinsic and intrinsic apoptosis pathways. There has been a debate about the effect of FUT8/CF on cell apoptosis in different types of cell and tissue as some researchers reported promotion [66][67][68] , and one reported inhibition [69] . However, whether it was the reason of the inhibited capacity of FUT8 low-expressing CAFs remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…l ‐Fucose‐specific lectins are powerful tools used in the laboratory diagnosis of major human malignancies including leukemia, SW480 colon cancer, and stomach and breast carcinomas among others . Fucosyltransferases (FucTs) are responsible for accelerating malignant transformation by means of fucosylation of sialylated precursors; that is, the formation and development of cancer cells require crucial fucoses, offering the basis for l ‐fucose‐mediated drug delivery to target hepatocellular carcinoma (HCC) cells as a therapeutic strategy . l ‐Fucose‐anchored methotrexate‐loaded solid lipid nanoparticles (SLNs) have been designed to target breast cancer, and it was found that relative to free drug, in vivo maximum bioavailability and tumor targeting efficiency markedly increased, together with the minimum secondary drug distribution in various organs with the formulated and anchored nanocarrier .…”
Section: Targeting Properties Of Mono‐ and Disaccharidesmentioning
confidence: 99%